High-adaptability sludge curing agent and application

By using highly adaptable sludge curing agents, combined with glass powder, latex powder, high water absorption resin and aggregate, the problem of insufficient performance of sludge curing agents in the prior art is solved, and high strength, durability and good water permeability are achieved. Permeable brick preparation.

CN119461935APending Publication Date: 2025-02-18JINAN JINYUE HIGHWAY ENGINEERING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411617913.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the dry shrinkage of the sludge curing agent is large, the water resistance is poor, the long settling period is long, the curing strength is relatively weak and the durability is insufficient, resulting in poor mechanical and water permeability of the water permeable bricks.

Method used

A highly adaptable sludge curing agent is used, which includes 1-8 parts of glass powder, 15-30 parts of latex powder, 10-18 parts of high water-absorbent resin, and 40-60 parts of aggregate based on mass parts. The curing agent improves the microstructure and chemical reaction of the sludge through the combination of glass powder, latex powder, high-water absorption resin and aggregate, and improves the curing strength and water permeability.

Benefits of technology

It achieves a firm combination of sludge particles to generate high-strength and durable permeable bricks, which have good mechanical properties, permeability and water storage properties, and can remove heavy metals and organic matters to prevent the dissolution of harmful substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461935A_ABST
    Figure CN119461935A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to a high-adaptability sludge curing agent and application thereof.Through the synergistic effect of glass powder, latex powder, super absorbent resin and graded aggregate, all unit phase interfaces of sludge particles can be firmly combined and can react with active substances in the sludge particles to generate expanded gelling substances, and the curing effect of the sludge particles is improved; through chemical excitation, combination and physical combination can be generated to improve the plasticity of a blank, the strength of a semi-finished green brick and the compressive strength of a product, the use performance of the product can be met, meanwhile, heavy metal and organic matter can be removed, harmful substances are prevented from being dissolved out, the raw materials are wide in source, the production process is simple, and the production cost is low. The unfired water permeable brick meeting the market requirement is produced by utilizing the desilted sludge on the premise of low energy consumption and no environmental pollution, so that the dual purposes of dredging the river channel, beautifying the water area environment and turning waste into wealth are achieved, and the unfired water permeable brick can be widely popularized and used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a highly adaptable sludge solidifying agent and application thereof. Background Art

[0002] Silt generally has the characteristics of high water content and low strength. If it is directly piled up or landfilled without effective utilization, it will occupy a large amount of land resources. In addition, river silt is polluted to a large extent, especially the silt in urban rivers, which contains a large amount of organic matter and nutrients such as nitrogen, phosphorus and other nutrients and some heavy metals, pathogens, viral microorganisms and toxic organic matter that are harmful to the ecological environment. These toxic and harmful substances make the silt easy to stink and rot. If it is not properly treated and directly discharged into the mud yard, it is easy to cause secondary pollution to the environment. In particular, stacking it on cultivated land will affect the effect of later reclamation, thereby increasing the difficulty of renting cultivated land.

[0003] Permeable bricks are a new environmentally friendly building material product of the century that was born to solve the problem of urban surface hardening, create a high-quality natural living environment, and maintain the ecological balance of the city. It is of great significance to effectively treat the waste sludge and convert it into permeable bricks for reuse through sludge solidification technology. Most of the permeable bricks in the existing technology use the traditional sintering method to make permeable bricks. This method is not only energy-intensive, but also causes certain pollution to the environment. In order to avoid the energy waste and air pollution caused by high-temperature sintering, unfired bricks have emerged, but unfired bricks are mainly formed by pressure pressing, and their internal bonding strength is low, resulting in the mechanical properties of unfired bricks being not as good as those of sintered bricks. Although increasing the pressure of pressing can improve the mechanical properties of unfired bricks, the increase in pressure will lead to a decrease in the internal porosity of unfired bricks, which in turn affects the permeability of unfired bricks.

[0004] At present, there have been many studies on modifiers for dredged sludge solidification, which are still mainly inorganic materials such as cement, quicklime and fly ash. However, they have problems such as large shrinkage, poor water resistance, long setting period, relatively weak solidification strength and insufficient durability. Therefore, it is of great significance to develop a sludge solidification material with strong adaptability that can make the sludge-converted unfired permeable bricks have both good mechanical properties and permeability and water storage properties. Summary of the invention

[0005] In order to overcome the above-mentioned technical defects, the present invention provides a highly adaptable sludge solidifying agent and its application, which is suitable for various types of typical sludges and solves the problems of poor hydration environment, insufficient Ca, uncoordinated generation rate and weakened distribution of hydration products, loose soil microstructure, insufficient strength and durability, poor permeability, and easy leaching of heavy metal ions in the solidification of cement-based sludge.

[0006] One of the purposes of the present invention is to provide a highly adaptable sludge solidifying agent, which comprises, by weight, 1-8 parts of glass powder, 15-30 parts of latex powder, 10-18 parts of highly absorbent resin, and 40-60 parts of aggregate.

[0007] In some specific embodiments, the glass powder is included in parts by mass, such as 1-6 parts, or 1-3 parts, or 2-7 parts, or 4-6 parts; latex powder is 15-25 parts, or 15-20 parts, or 18-28 parts, or 21-26 parts; super absorbent resin is 10-16 parts, or 10-14 parts, or 12-15 parts; aggregate is 40-55 parts, or 40-50 parts, or 40-45 parts, or 43-47 parts, or 48-53 parts, or 56-60 parts.

[0008] In some specific embodiments, the particle size of the glass powder is 60-90 μm, or 65-85 μm; preferably, 70-75 μm.

[0009] In some specific embodiments, the latex powder is a mixture of one or more of polyacetate / vinyl ester latex powder, acrylic latex powder, and styrene-butadiene latex powder.

[0010] In some specific embodiments, the super absorbent resin is selected from one or a mixture of sodium polyacrylate, potassium polyacrylate, polyacrylamide, and polyacrylacetamide.

[0011] In some specific embodiments, the aggregate is fine aggregate and coarse aggregate in a mass ratio of 1-10; the particle size of the fine aggregate is 200 μm-2 mm; and the particle size of the coarse aggregate is 4 mm-12 mm.

[0012] In some specific embodiments, the mass ratio of the fine aggregate to the coarse aggregate is 1-8, or the mass ratio is 1-5, or the mass ratio is 3-9, or the mass ratio is 5-7.

[0013] In some specific embodiments, the particle size of the fine aggregate is 200μm-1mm, or 200-800μm, or 200-600μm, or 200-300μm, or 250-450μm, or 550-750μm, or 850μm-1mm; the particle size of the coarse aggregate is 4mm-10mm, or 4-8mm, or 4-6mm, or 5-9mm, or 5-7mm.

[0014] The second object of the present invention is to provide the effect of the above-mentioned sludge solidifying agent in preparing sludge unfired permeable bricks, comprising the following steps:

[0015] S1. After removing large particles or impurities from the sludge, it is aged and dehydrated to a moisture content of 35-55%;

[0016] S2. Stir 70-80 parts by weight of silt, 5-18 parts by weight of cement, and 25-30 parts by weight of silt solidifier until they are evenly mixed, and then wheel roll; use a lower cement content in combination with the silt solidifier to chemically excite the cementitious material to produce a superposition effect, and at the same time, by crushing the glass structure in the silt, the SiO2 and Al2O3 in the glass can be precipitated, so that the material can be more fully in contact with the active stimulator, produce an excitation effect, and convert more active components in the silt into hydration products such as silicates and aluminates.

[0017] S3. The raw material rolled by the wheel is fed into the molding machine for cutting and molding;

[0018] S4. The cut raw materials are sent to the steam curing room, the steam temperature is 90-110 ° C, the pressure is 0.05-1MPa, and the curing time is 12-24h;

[0019] In some specific embodiments, the blocks are naturally cured for 1-5 hours before being sent to the steam curing chamber.

[0020] S5. Place the steam-cured brickwork under natural conditions for 3-7 days to obtain the finished product.

[0021] The curing agent of the present invention has the construction feasibility of replacing ordinary silicate cement, can be mixed with soil to form a solidified soil member with sufficient strength and meeting the permeability requirements, effectively improve the deformation characteristics of the original soil, and use dredged sludge to produce unfired permeable bricks that meet market demand under the premise of low production cost, simple production process, low energy consumption and no environmental pollution, thereby achieving the dual purposes of dredging rivers, beautifying the water environment and turning waste into treasure.

[0022] In some specific embodiments, the compressive strength of the permeable brick is 18-25 MPa, the water absorption rate is 9-13%, and the water retention is 0.45-0.8 g / cm 2 .

[0023] Beneficial effects: Compared with the prior art, the sludge solidifying agent of the present invention can firmly bond the interfaces of each unit of sludge particles, and can react with the active substances in the sludge particles to generate expanded gelling substances. It can produce bonding through chemical excitation and physical bonding, so that the strength and stability of the consolidated soil can meet the actual requirements of the project. At the same time, it can also remove heavy metals and organic matter and prevent the dissolution of harmful substances. The raw materials of the present invention are widely available, and engineering waste and riverbed dredged sludge are fully utilized. It is low-cost, pollution-free, and can be widely promoted and used. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the SEM picture of the soil after adding silt and solidifying agent;

[0025] Figure 2 The present invention discloses a solidified water-permeable brick. DETAILED DESCRIPTION

[0026] In order to make those skilled in the art better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments. The experimental methods in the following examples that do not specify specific conditions are usually based on conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, percentages and parts are calculated by weight. Unless otherwise defined, all professional and scientific terms used in the text have the same meanings as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the recorded content can be applied to the present invention. The preferred implementation methods and materials described in the text are for demonstration purposes only.

[0027] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] Based on the present invention, the sludge solidifying agent with high adaptability comprises, by weight, 1-8 parts of glass powder, 15-30 parts of latex powder, 10-18 parts of highly absorbent resin and 40-60 parts of aggregate.

[0029] In actual operation, since glass powder has a high alkali content, fine glass powder is used to replace quicklime as an alkaline activator to increase the alkalinity of the slurry and reduce Ca 2+ The solubility of ions can improve the early strength of the mixed slurry. The latex powder can improve the cracking performance of the solidified soil itself. For clay with a high plasticity index, the problem of large shrinkage of the solidified soil is solved. The use of high-performance water-absorbent resin can quickly reduce the moisture content of the sludge, solving the problem that the traditional sludge solidifier cannot reach the designed strength due to the moisture content. At the same time, the hydration products formed by the water absorption process of the high-performance water-absorbent resin can fix harmful heavy metals such as lead, chromium, and copper, reducing the secondary pollution caused by the sludge. By using glass powder, latex powder, high water-absorbent resin, and aggregate to improve the plasticity of the blank, the strength of the semi-finished brick blank, and the compressive strength of the product, it can not only meet the performance of the product, but also fully meet the requirements of national standards.

[0030] In some specific embodiments, the glass powder is included in parts by mass, such as 1-6 parts, or 1-3 parts, or 2-7 parts, or 4-6 parts; latex powder is 15-25 parts, or 15-20 parts, or 18-28 parts, or 21-26 parts; super absorbent resin is 10-16 parts, or 10-14 parts, or 12-15 parts; aggregate is 40-55 parts, or 40-50 parts, or 40-45 parts, or 43-47 parts, or 48-53 parts, or 56-60 parts.

[0031] In some specific embodiments, the particle size of the glass powder is 60-90 μm, or 65-85 μm; preferably, 70-75 μm.

[0032] In some specific embodiments, the latex powder is a mixture of one or more of polyacetate / vinyl ester latex powder, acrylic latex powder, styrene-butadiene latex powder, etc. One or more of the following latex powders can be selected: Wacker latex powder 5044N, Wacker latex powder 5010N, Wacker latex powder 5011L, Wacker latex powder 7055N.

[0033] In some specific embodiments, the super absorbent resin is selected from one or a mixture of sodium polyacrylate, potassium polyacrylate, polyacrylamide, and polyacrylamide. One or more of the following resins can be selected: PM-01230 of Guangdong Pullman New Material Technology Co., Ltd. and H-106 of Fuhe New Material Technology (Shanghai) Co., Ltd.

[0034] In some specific embodiments, the aggregate is a fine aggregate and a coarse aggregate with a mass ratio of 1-10; the particle size of the fine aggregate is 200 μm-2 mm; the particle size of the coarse aggregate is 4 mm-12 mm. In specific practice, the aggregate particles are scientifically graded to make the internal pore distribution of the solidified soil reasonable, which not only improves the mechanical properties of the product, but also maintains a high permeability coefficient and water storage capacity.

[0035] In some specific embodiments, the mass ratio of the fine aggregate to the coarse aggregate is 1-8, or the mass ratio is 1-5, or the mass ratio is 3-9, or the mass ratio is 5-7.

[0036] The coarse aggregate shall meet the performance indicators specified in GB / T14685-2011 "Pebble and crushed stone for construction", and the fine aggregate shall meet the performance indicators specified in GB / T14684-2011 "Sand for construction".

[0037] In some specific embodiments, the particle size of the fine aggregate is 200μm-1mm, or 200-800μm, or 200-600μm, or 200-300μm, or 250-450μm, or 550-750μm, or 850μm-1mm; the particle size of the coarse aggregate is 4mm-10mm, or 4-8mm, or 4-6mm, or 5-9mm, or 5-7mm.

[0038] The second object of the present invention is to provide the effect of the above-mentioned sludge solidifying agent in preparing sludge unfired permeable bricks, comprising the following steps:

[0039] S1. After removing large particles or impurities from the sludge, it is aged and dehydrated to a moisture content of 35-55%;

[0040] The silt is one or more of river and lake channel silt, ocean tidal flat silt, box culvert silt and dredged mud;

[0041] S2. Stir 70-80 parts by mass of sludge, 5-18 parts by mass of cement, and 25-30 parts by mass of sludge curing agent until uniformly mixed, and roll;

[0042] The cement is one or more of grade 32.5 and grade 42.5;

[0043] A lower cement content is used in combination with a sludge solidifier to chemically stimulate the cementitious material to produce a superposition effect. At the same time, the glass structure in the sludge is crushed so that SiO2 and Al2O3 in the glass can be precipitated. In this way, the material can be more fully in contact with the active stimulator, producing an excitation effect and converting more active components in the sludge into hydration products such as silicates and aluminates.

[0044] S3. The raw material rolled by the wheel is fed into the block forming machine for block forming;

[0045] S4. The cut raw materials are sent to the steam curing room, the steam temperature is 90-110 ° C, the pressure is 0.05-1MPa, and the curing time is 12-24h;

[0046] In some specific embodiments, the blocks are naturally cured for 1-5 hours before being sent to the steam curing chamber.

[0047] S5. Place the steam-cured brickwork under natural conditions for 3-7 days to obtain the finished product (such as Figure 2 shown).

[0048] SEM images of pure sludge and sludge mixed with additives are shown in the figure below. Figure 1 As shown, Figure 1 a is the sample formed by pure sludge matrix, in which the particles are distributed independently, the gaps between particles are large, and there is no connection between them, so the structural stability is poor; Figure 1 In Figure b, we can see that more hydration products are generated around the Si-O tetrahedrons of the silt particles: CSH(B), C2SH, and C2SH2. On the one hand, these hydration products play a cementing role, connecting independent silt particles to present a network skeleton structure, and the overall structural integrity is significantly enhanced; on the other hand, they fill the gaps between the silt particles, making the internal structure of the test sample more compact and stable.

[0049] The curing agent of the present invention has the construction feasibility of replacing ordinary silicate cement, can be mixed with soil to form a solidified soil component with sufficient strength and meeting the permeability requirements, effectively improve the deformation characteristics of the original soil, and use dredged sludge to produce unfired permeable bricks that meet market demand under the premise of low production cost, simple production process, low energy consumption and no environmental pollution, which can dredge rivers, beautify the water environment and turn waste into treasure.

[0050] In some specific embodiments, the permeable bricks have a compressive strength of 18-25 MPa, a water absorption rate of 9-13%, and a water retention of 0.45-0.8 g / cm 2 .

[0051] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0052] Example 1

[0053] A sludge solidifying agent, by weight, 8 parts of glass powder, 28 parts of latex powder, 18 parts of highly absorbent resin, and 60 parts of aggregate are mixed evenly;

[0054] The particle size of the glass powder is 70-75 μm, the latex powder is Wacker latex powder 5044N, the super absorbent resin is PM-01230, and the aggregate is fine aggregate and coarse aggregate in a mass ratio of 3.

[0055] Example 2

[0056] A sludge solidifying agent, by weight, 6 parts of glass powder, 26 parts of latex powder, 15 parts of highly absorbent resin, and 53 parts of aggregate are mixed evenly;

[0057] The particle size of the glass powder is 70-75 μm, the latex powder is Wacker latex powder 5044N, the super absorbent resin is H-106, and the aggregate is fine aggregate and coarse aggregate with a mass ratio of 8.

[0058] Example 3

[0059] A sludge solidifying agent, by weight, 4 parts of glass powder, 15 parts of latex powder, 14 parts of highly absorbent resin, and 45 parts of aggregate are mixed evenly;

[0060] The particle size of the glass powder is 70-75 μm, the latex powder is Wacker latex powder 5044N, the super absorbent resin is PM-01230, and the aggregate is fine aggregate and coarse aggregate with a mass ratio of 5.

[0061] Example 4

[0062] A sludge solidifying agent, calculated by weight, is prepared by mixing 3 parts of glass powder, 28 parts of latex powder, 10 parts of highly absorbent resin, and 56 parts of aggregate evenly;

[0063] The particle size of the glass powder is 70-75 μm, the latex powder is Wacker latex powder 5011L, the super absorbent resin is H-106, and the aggregate is fine aggregate and coarse aggregate with a mass ratio of 7.

[0064] Example 5

[0065] A sludge solidifying agent, by weight, 7 parts of glass powder, 21 parts of latex powder, 12 parts of highly absorbent resin, and 47 parts of aggregate are mixed evenly;

[0066] The particle size of the glass powder is 70-75 μm, the latex powder is Wacker latex powder 5011L, the super absorbent resin is PM-01230, and the aggregate is fine aggregate and coarse aggregate with a mass ratio of 9.

[0067] Example 6

[0068] A sludge solidifying agent, by weight, 6 parts of glass powder, 18 parts of latex powder, 15 parts of highly absorbent resin, and 53 parts of aggregate are mixed evenly;

[0069] The particle size of the glass powder is 70-75 μm, the latex powder is Wacker latex powder 5011L, the super absorbent resin is H-106, and the aggregate is fine aggregate and coarse aggregate in a mass ratio of 3.

[0070] Example 7 Application of sludge solidifying agent

[0071] The sludge solidifying agent prepared in the above embodiment 1 is used to convert the high-water content sludge in urban sewage treatment plants and rivers and lakes into permeable bricks. The specific preparation method is: take the sludge and remove large particles or impurities, then age and dehydrate it, detect the water content, and pass it through a 200-mesh sieve for standby use; stir the sludge, cement, and sludge solidifying agent by weight until they are evenly mixed, and roll them; after mixing and stirring the above materials evenly, put them into a mold, and use a press to preform at 20MPa for 12 seconds; the preformed blocks are naturally cured for 3 hours and then sent to an autoclave curing workshop, and cured for 15 hours at a steam temperature of 110°C and a pressure of 0.35MPa; the steam-cured bricks are placed under natural conditions for 3-7 days to obtain the finished product; each component is calculated by weight, 70 parts of sludge (water content is 45%), 18 parts of cement, and 25 parts of sludge solidifying agent.

[0072] Example 8

[0073] The difference compared with Example 7 is that the sludge curing agent of Example 2 is used to prepare permeable bricks, and the components are calculated by weight: 70 parts of sludge (water content is 55%), 10 parts of cement, and 30 parts of sludge curing agent.

[0074] Example 9

[0075] The difference compared with Example 7 is that the sludge curing agent of Example 3 is used to prepare permeable bricks, and the components are calculated by weight: 80 parts of sludge (water content is 50%), 5 parts of cement, and 30 parts of sludge curing agent.

[0076] Example 10

[0077] The difference compared with Example 7 is that the sludge curing agent of Example 4 is used to prepare permeable bricks, and the components are calculated by weight: 80 parts of sludge (water content is 45%), 10 parts of cement, and 25 parts of sludge curing agent.

[0078] Embodiment 11

[0079] The difference compared with Example 7 is that the sludge curing agent of Example 5 is used to prepare permeable bricks, and the components are calculated by weight: 75 parts of sludge (water content is 50%), 12 parts of cement, and 25 parts of sludge curing agent.

[0080] Example 12

[0081] The difference compared with Example 7 is that the sludge curing agent of Example 6 is used to prepare permeable bricks, and the components are calculated by weight: 75 parts of sludge (water content is 55%), 15 parts of cement, and 30 parts of sludge curing agent.

[0082] Comparative Example 1

[0083] The same as Example 7, except that the glass powder is replaced by fly ash.

[0084] Comparative Example 2

[0085] The same as Example 8, except that the glass powder is replaced with 10-25 mm glass powder.

[0086] Comparative Example 3

[0087] Same as Example 9, except that no latex powder is added.

[0088] Comparative Example 4

[0089] The same as Example 10, except that the super absorbent resin is replaced by cement.

[0090] Comparative Example 5

[0091] Same as Example 11, except that no coarse aggregate is added.

[0092] Comparative Example 6

[0093] Same as Example 12, except that no fine aggregate is added.

[0094] The permeable bricks prepared in the embodiment and the comparative example were tested for compressive strength, water absorption, water retention, SS, COD removal effect and heavy metal solidification effect, and the results were shown in the following table:

[0095]

[0096] As can be seen from the above table, the compressive strength, water absorption rate and water retention of the silt permeable bricks prepared in Examples 7-12 are higher than the corresponding performances of the permeable bricks prepared in Comparative Examples 1-6. In Comparative Examples 1-2, fly ash and coarse glass powder are used as active admixtures respectively. Compared with Examples 7-8, the hydration effect is relatively weak, resulting in weaker strength of the permeable bricks; compared with Comparative Examples 3-4, the cohesion of the solidified soil in Examples 9-10 is significantly greater than that of the cement soil, and the high-performance water-absorbing resin can quickly reduce the moisture content of the silt and improve the strength of the permeable bricks; the internal aggregate gradation of the permeable bricks obtained in Comparative Examples 5-6 is unreasonable, resulting in lower strength of the finished bricks, and poor permeability and water storage. The water-absorbent resin and latex powder added to the permeable bricks prepared in the embodiments of the present invention absorb a large amount of water molecules in the surrounding pores, so that the unfired bricks have a certain water permeability and can discharge water from the internal permeable channels in a short time, while also improving the water storage performance; compared with comparative examples 3-4, embodiments 9-10 have low heavy metal leaching amounts, which shows that the addition of high-performance water-absorbent resin has better adsorption effect and good heavy metal solidification effect.

[0097] Finally, it should be noted that the above description is only a preferred embodiment of the present invention. Under the guidance of the present invention, those skilled in the art can make a variety of similar expressions without violating the purpose and claims of the present invention, and such changes all fall within the protection scope of the present invention.

Claims

1. A highly adaptable sludge solidifying agent, characterized in that: Calculated by weight, it includes 1-8 parts of glass powder, 15-30 parts of latex powder, 10-18 parts of highly absorbent resin, and 40-60 parts of aggregate.

2. The sludge solidifying agent according to claim 1, characterized in that Calculated by weight, it includes 1-6 parts of the glass powder, or 1-3 parts, or 2-7 parts, or 4-6 parts; 15-25 parts of latex powder, or 15-20 parts, or 18-28 parts, or 21-26 parts; 10-16 parts of super absorbent resin, or 10-14 parts, or 12-15 powder; 40-55 parts of aggregate, or 40-50 parts, or 40-45 parts, or 43-47 parts, or 48-53 parts, or 56-60 parts.

3. The sludge solidifying agent according to claim 1, characterized in that The particle size of the glass powder is 60-90 μm, or 65-85 μm; preferably, 70-75 μm.

4. The sludge solidifying agent according to claim 1, characterized in that The latex powder is one or a mixture of polyacetate / vinyl ester latex powder, acrylic latex powder and styrene-butadiene latex powder.

5. The sludge solidifying agent according to claim 1, characterized in that: The highly absorbent resin is selected from one of sodium polyacrylate, potassium polyacrylate, polyacrylamide, and polyacrylacetamide, or a mixture of the two or more thereof.

6. The sludge solidifying agent according to claim 1, characterized in that: The aggregates are fine aggregate and coarse aggregate in a mass ratio of 1-10; the particle size of the fine aggregate is 200 μm-2 mm; and the particle size of the coarse aggregate is 4 mm-12 mm.

7. The sludge solidifying agent according to claim 6, characterized in that: The mass ratio of the fine aggregate to the coarse aggregate is 1-8, or 1-5, or 3-9, or 5-7.

8. The sludge solidifying agent according to claim 6, characterized in that: The particle size of the fine aggregate is 200 μm-1 mm, or 200-800 μm, or 200-600 μm, or 200-300 μm, or 250-450 μm, or 550-750 μm, or 850 μm-1 mm; the particle size of the coarse aggregate is 4 mm-10 mm, or 4-8 mm, or 4-6 mm, or 5-9 mm, or 5-7 mm.

9. Use of the sludge solidifying agent according to any one of claims 1 to 8 in the preparation of sludge unfired permeable bricks, characterized in that: The following steps are involved: S1. After removing large particles or impurities from the sludge, it is aged and dehydrated to a moisture content of 35-55%; S2. Stir 70-80 parts by mass of sludge, 5-18 parts by mass of cement, and 25-30 parts by mass of sludge curing agent until uniformly mixed, and roll; S3. The raw material rolled by the wheel is fed into the block forming machine for block forming; S4. The cut raw materials are sent to the steam curing room, the steam temperature is 90-110 ° C, the pressure is 0.05-1MPa, and the curing time is 12-24h; S5. Place the steam-cured brickwork under natural conditions for 3-7 days to obtain the finished product.

10. The use according to claim 9, characterized in that: The permeable brick has a compressive strength of 18-25 MPa, a water absorption rate of 9-13%, and a water retention of 0.45-0.8 g / cm 2 .